Estimation of wildlife-inflicted property damage and abatement based on compensation program claims data. - Yoder, Jonathan (Land Economics, 2002)
Wildlife imposes costs on agricultural landowners in the form of damage to crops, livestock, and other property, and some wildlife agencies maintain abatement and compensation programs. This paper incorporates endogenous claim submission by producers into a model of deer-inflicted crop damage that can be used to facilitate agency decisions regarding deer densities and distribution, abatement use, and to forecast compensation budgets. The model is applied to field-level compensation claims data from Wisconsin for 1994-1996. The results are consistent with theory, and aggregate damage estimates fall within the range of published estimates from more costly survey data. Reprinted by permission of the publisher.